High hopes: Altitude training for swimmers - Stott, M. (Swimming World Magazine, 2000)
Opinion on the benefits of high altitude training is extremely divided. Respected scientists, physiologists, coaches and swimmers respectfully/disrespectfully agree/disagree on altitude training usefulness, physiological effects and individual response. Considerable research, countless papers and hundreds of thousands of observation hours by the brightest coaching minds in the world come to different conclusions. Reconcile these two items with the statement that follows them: Participants of USA Swimming's National Team Camp went to 13,000 feet in October to participate in leadership and team building. Chad Carvin trained with the Mission Viejo Nadadores in Colorado Springs for nearly three weeks in November and December. Three days later in College Park, Md., unshaved and untapered, he set an American record of 3:42.16 in the 400 meter (sc) free. And, now, the statement: "Although the field contains many studies, those which are definitive lead to the conclusion that altitude training is not an avenue for enhancing sea-level performances of highly-trained swimmers. The practice of conducting altitude training camps for highly elite swimmers is not justified either on physiological grounds or performance benefits," writes Professor Brent S. Rushall and colleagues at San Diego State University and the University of Canberra in Australia. Heresy or reality? Opinion on this subject is extremely divided. Yet, thriving businesses on three continents are based on the concept as are training regimens by some of the world's best swimming coaches for their athletes. If ever there were a field for further examination, the effects of altitude on athletic training qualifies to be at the top of the list.